Edukasi Keuangan Dan Bisnis Digital Strategi Membangun Kemandirian Financial Sejak Dini Pada Siswa Sekolah Menengah Atas Di Desa Menur - Umar, Aqib; Cantika Salma Azzahra; Naili Sa’adah; Daimatul Ilma Luthfia; Zakiyya Zulfa; Lailin Faiza Ayuni; Chusniatun Nadhifah; Norma Ayuningrum; Nazalatun Najwa (LPPM UNINUS, 2025)
The gap in financial literacy and the lack of digital entrepreneurship understanding among students pose challenges in shaping a financially independent generation. This community service activity aimed to improve students’ financial literacy and entrepreneurial skills through interactive seminars and digital-based packaging design training. The implementation method included participatory-educational approaches during material presentation, the use of a pretest-posttest method to assess participants’ understanding before and after the financial literacy session, and a graphic design workshop using Canva. The evaluation results showed a significant increase in participants’ understanding scores before and after the activity, as well as improved creativity in the packaging design outputs. The conclusion of this activity is that financial literacy education and graphic design training can effectively enhance students’ awareness and practical skills in facing the challenges of the digital economy, while also fostering independence and entrepreneurial spirit from an early age.